Ответ:
1) [tex]7+m[/tex]
2) [tex]\frac{1}{x -1}[/tex]
3) [tex]\frac{5}{x+y}[/tex]
4) [tex]\frac{5}{a-b}[/tex]
Объяснение:
1)
[tex]\frac{49}{7-m} -\frac{m2}{7-m} =\frac{49-m^{2} }{7-m} =\frac{(7-m)(7+m)}{7-m} =7+m[/tex]
2)
[tex]\frac{x+7}{x^{2} -1} -\frac{6}{x^{2} -1} =\frac{x+7-6}{x^{2} -1} =\frac{x+1}{x^{2} -1} =\frac{x+1}{(x-1)(x+1)} =\frac{1}{x -1}[/tex]
3)
[tex]\frac{5x-2}{x^{2} -y^{2}} -\frac{5y-2}{x^{2} -y^{2}} =\frac{5x-2-(5y-2)}{x^{2} -y^{2}} =\frac{5x-2-5y+2}{x^{2} -y^{2}} =\frac{5x-5y}{x^{2} -y^{2}} =\frac{5(x-y)}{(x-y)(x+y)} =\frac{5}{x+y}[/tex]
4)
[tex]\frac{3a-4b}{(a-b)^{2}} +\frac{2a-b}{(a-b)^{2}} =\frac{3a-4b+(2a-b)}{(a-b)^{2}} =\frac{3a-4b+2a-b}{(a-b)^{2}}= \frac{5a-5b}{(a-b)^{2}} =\frac{5(a-b)}{(a-b)(a-b)} =\frac{5}{a-b}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1) [tex]7+m[/tex]
2) [tex]\frac{1}{x -1}[/tex]
3) [tex]\frac{5}{x+y}[/tex]
4) [tex]\frac{5}{a-b}[/tex]
Объяснение:
1)
[tex]\frac{49}{7-m} -\frac{m2}{7-m} =\frac{49-m^{2} }{7-m} =\frac{(7-m)(7+m)}{7-m} =7+m[/tex]
2)
[tex]\frac{x+7}{x^{2} -1} -\frac{6}{x^{2} -1} =\frac{x+7-6}{x^{2} -1} =\frac{x+1}{x^{2} -1} =\frac{x+1}{(x-1)(x+1)} =\frac{1}{x -1}[/tex]
3)
[tex]\frac{5x-2}{x^{2} -y^{2}} -\frac{5y-2}{x^{2} -y^{2}} =\frac{5x-2-(5y-2)}{x^{2} -y^{2}} =\frac{5x-2-5y+2}{x^{2} -y^{2}} =\frac{5x-5y}{x^{2} -y^{2}} =\frac{5(x-y)}{(x-y)(x+y)} =\frac{5}{x+y}[/tex]
4)
[tex]\frac{3a-4b}{(a-b)^{2}} +\frac{2a-b}{(a-b)^{2}} =\frac{3a-4b+(2a-b)}{(a-b)^{2}} =\frac{3a-4b+2a-b}{(a-b)^{2}}= \frac{5a-5b}{(a-b)^{2}} =\frac{5(a-b)}{(a-b)(a-b)} =\frac{5}{a-b}[/tex]